Standards of Practice in Domestic and Family Violence Behaviour Change Programs in Australia and New Zealand - Day, A.; Vlais, R.; Chung, Donna; Green, D. (Australian Academic Press, 2018)
Domestic and family violence is a key area of concern for all professionals who work with families, with recent years seeing an expansion in the availability of intervention programs for men who perpetrate violence against women and children. This paper considers current approaches to the regulation of professional practice in this area, providing information about the changing context in which interventions are offered. The purpose of the paper is to encourage ongoing discussion about the setting of men's behaviour change program standards of practice in Australasia and to identify some key issues that require consideration.